COVID-19 and small businesses - Ronen Harel (Archives of Community Medicine and Public Health - Peertechz Publications, 2021)
In December 2019, the global health crisis caused by the Coronavirus Disease (COVID-19) began in China, catching the world unawares and unprepared [1]. COVID-19, which was declared a global pandemic by the World Health Organization [2], has infected now more than 125 million persons and caused more than 2.5 million deaths as of February, 2021 [3]. The efforts of governments around the globe to reduce the transmission of the disease led to a lockdown of communities and business closures [4] and caused significant damage to large portion of business activities.